Oral microbiome changes associated with the menstrual cycle in healthy young adult females - Yamazaki, Ayaka; Ogura, Kohei; Minami, Kana; Ogai, Kazuhiro; Horiguchi, Tomomi; Okamoto, Shigefumi; Mukai, Kanae (Frontiers in Cellular and Infection Microbiology, 2023)
The relationship between the menstrual cycle and the oral microbiome has not been clarified. The purpose of this study was to assess potential changes in the oral microbiome of healthy young adults using 16S rRNA-based sequencing. Eleven females (aged 23–36 years) with stable menstrual cycles and without any oral problems were recruited. Saliva samples were collected before brushing every morning during the menstrual period. Based on basal body temperatures, menstrual cycles were divided into four phases, namely the menstrual, follicular, early luteal, and late luteal phases. Our results showed that the follicular phase had a significantly higher abundance ratio of the Streptococcus genus than the early and late luteal phases, whereas the abundance ratios of the Prevotella 7 and Prevotella 6 genera were significantly lower in the follicular phase than those in the early and late luteal phases and that in the early luteal phase, respectively. Alpha diversity by the Simpson index was significantly lower in the follicular phase than that in the early luteal phase, and beta diversity showed significant differences among the four phases. Using the relative abundance data and copy numbers of the 16S rRNA genes in the samples, the bacterial amounts in the four phases were compared, and we observed that the follicular phase had significantly lower amounts of the Prevotella 7 and Prevotella 6 genera than the menstrual and early luteal phase, respectively. These results indicate reciprocal changes with the Streptococcus genus and Prevotella genera, particularly in the follicular phase. In the present study, we showed that the oral microbiome profiles are affected by the menstrual cycles of healthy young adult females.